STRATEGI PENGEMBANGAN JASA LINGKUNGAN EKOWISATA DIWILAYAH SEMI ARID NUSA TENGGARA TIMUR - Aah Ahmad Almulqu; Kristina Sinaldi; Haryadi Darmawan (Universitas 17 Agustus 1945 Samarinda, 2024)
Taman Wisata Alam (TWA) Baumata is one of the natural tourism located in Kupang. The purpose of this study is to analyze the TWA Baumata current performance towards competitors, analyzing the strengths and weaknesses factors, as well as opportunities and threats of the TWA Baumata. Lastly, formulates a proper alternative strategy for the TWA Baumata. Based on the results of qualitative analysis, the TWA Baumata current performance, there are remain several aspects that need to be improved. The SWOT matrix analysis generates several alternative strategies, including: resource management related to zoning, area function boundaries, improving infrastructure, optimizing natural potential, and capacity development of local communities to actively participate in TWA Baumata management.